2020
DOI: 10.3389/fnut.2020.00044
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition, Health and the Role of Machine Learning in Clinical Setting

Abstract: Nutrition plays a vital role in health and the recovery process. Deficiencies in macronutrients and micronutrients can impact the development and progression of various disorders. However, malnutrition screening tools and their utility in the clinical setting remain largely understudied. In this study, we summarize the importance of nutritional adequacy and its association with neurological, cardiovascular, and immunerelated disorders. We also examine general and specific malnutrition assessment tools utilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 77 publications
(63 reference statements)
2
12
0
1
Order By: Relevance
“…Populations with a higher disability 18 and lower median income 19 might be less mobile, have more comorbidities, 20,21 and also less likely benefit from timely high-quality care 22 and high-quality nutrition; all of these factors could be equally important to combating this pandemic. 23,24 Furthermore, our analysis of the preliminary data on mobility, given the recent social distancing guidelines, corroborate the impact of this intervention on lowering the infection rate and death.…”
Section: Discussionsupporting
confidence: 72%
“…Populations with a higher disability 18 and lower median income 19 might be less mobile, have more comorbidities, 20,21 and also less likely benefit from timely high-quality care 22 and high-quality nutrition; all of these factors could be equally important to combating this pandemic. 23,24 Furthermore, our analysis of the preliminary data on mobility, given the recent social distancing guidelines, corroborate the impact of this intervention on lowering the infection rate and death.…”
Section: Discussionsupporting
confidence: 72%
“…Full risk factor description is available in Table 1 **Denotes statistically significant benefit from timely high-quality care [24] and high-quality nutrition; all of these factors could be equally important to combating this pandemic [25,26]. Furthermore, our analysis of the preliminary data on mobility, given the recent social distancing guidelines, corroborate the impact of this intervention on lowering the infection rate and death.…”
Section: E-04supporting
confidence: 56%
“…By adding the interaction terms in the linear regression model (death rate~poverty + disability + poverty:disability) of death rate, we do not observe a significant interaction ( p = 0.469), suggesting these two variables could be independent in their contribution to the risk of mortality. Populations with a higher disability [ 20 ] and lower median income [ 21 ] might be less mobile, have more comorbidities [ 22 , 23 ], and also less likely benefit from timely high-quality care [ 24 ] and high-quality nutrition; all of these factors could be equally important to combating this pandemic [ 25 , 26 ]. Furthermore, our analysis of the preliminary data on mobility, given the recent social distancing guidelines, corroborate the impact of this intervention on lowering the infection rate and death.…”
Section: Discussionmentioning
confidence: 99%
“…We have also performed a detailed analysis of our Geisinger cohort and identified that sex was not an independent risk factor for all-cause mortality and ischemic stroke recurrence ( 33 ). Finally, the identification of malnutrition provides potential new venues to improve secondary prevention and outcome ( 34 ).…”
Section: Discussionmentioning
confidence: 99%